Energy Efficiency in Industrial Processes, Talk - Schlüter, Alexander

Energie sparen mit Gas - Schlüter, Alexander; Rommel, Benjamin; Schäfer, Mirko; Hesselbach, Jens (energy 2.0)

Untersuchung des dynamischen Verhaltens gekoppelter piezoelektrischer Ultraschallmotoren mit Stoßkontakt - Mracek, Boris

A comparison of some efficient numerical methods for a nonlinear elliptic problem - Kovács, Balázs (Central European Journal of Mathematics)
Keywords: General Mathematics

Der Studiengang "Integrierte Sonderpädagogik" an der Universität Bielefeld. - Kottmann, Brigitte (Inklusion in Bildungsinstitutionen)

vel silvae maiores vel montium iuga - Die räumliche Erschließung Westfalens im frühen Mittelalter (7.-9. Jh.) - Englisch, Brigitte (Total Regional. Studien zur frühneuzeitlichen Sozial- und wirtschaftsgeschcihte. Festschrift für Frank Göttmann zum 65. Geburtstag)

Ostern zwischen Arianismus und Katholizismus. Zur Komputistik in den Reichen der Westgoten im 6. und 7. Jh. - Englisch, Brigitte (Proceedings of the 2nd International Conference on the Science of Computus in Ireland and Europe, Galway 11-13 July, 2008)

The Nexus between Monetary Policy, Banking Market Structure and Bank Risk Taking - Michalak, Tobias C.; Uhde, André
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.
Keywords: risk-taking channel; competition; concentration; bank soundness; European banking

Darstellen–Deuten–Darstellungen vernetzen: Ein fach-und sprachintegrierter Förderansatz für mehrsprachige Lernende im Mathematikunterricht - Prediger, Susanne; Wessel, Lena (Mathematiklernen unter Bedingungen der Mehrsprachigkeit–Stand und Perspektiven der Forschung und Entwicklung. Münster ua: Waxmann)

Relating registers for fractions–multilingual students on their way to conceptual understanding - Prediger, Susanne; Wessel, Lena (Proceedings of the ICMI Study 21 - Mathematics and Language Diversity)